Importance of WNT-dependent signaling for derivation and maintenance of primed pluripotent bovine embryonic stem cells. Issue 1 (23rd April 2021) - Xiao, Yao; Amaral, Thiago F; Ross, Pablo J; Soto, Delia A; Diffenderfer, Kenneth E; Pankonin, Aimee R; Jeensuk, Surawich; Tríbulo, Paula; Hansen, Peter J
Abstract: The WNT signaling system plays an important but paradoxical role in the regulation of pluripotency. In the cow, IWR-1, which inhibits canonical WNT activation and has WNT-independent actions, promotes the derivation of primed pluripotent embryonic stem cells from the blastocyst. Here, we describe a series of experiments to determine whether derivation of embryonic stem cells could be generated by replacing IWR-1 with other inhibitors of WNT signaling. Results confirm the importance of inhibition of canonical WNT signaling for the establishment of pluripotent embryonic stem cells in cattle and indicate that the actions of IWR-1 can be mimicked by the WNT secretion inhibitor IWP2 but not by the tankyrase inhibitor XAV939 or WNT inhibitory protein dickkopf 1. The role of Janus kinase-mediated signaling pathways for the maintenance of pluripotency of embryonic stem cells was also evaluated. Maintenance of pluripotency of embryonic stem cells lines was blocked by a broad inhibitor of Janus kinase, even though the cells did not express phosphorylated signal transducer and activator of transcription 3 (pSTAT3). Further studies with blastocysts indicated that IWR-1 blocks the activation of pSTAT3. A likely explanation is that IWR-1 blocks differentiation of embryonic stem cells into a pSTAT3+ lineage. In conclusion, results presented here indicate the importance of inhibition of WNT signaling for the derivation of pluripotent bovine embryonic stem cells, the role of Janus kinase signaling for maintenance of pluripotency, and the participation of IWR-1 in the inhibition of activation of STAT3. Abstract : Derivation of pluripotent embryonic stem cells from bovine blastocysts depends upon blocking WNT signaling; maintenance of pluripotency depends upon JAK signaling in a STAT3-independent manner.